Pengaruh Kualitas Produk Dan Brand Trust Terhadap Loyalitas Pelanggan Pada Produk Pelembab Wajah Bioaqua Di Kota Depok - Maylinda Nur Faizah; Rizal Bakti; Noviyanti Noviyanti (Teewan Journal Solutions, 2026)
The rapid growth of the skincare industry in Indonesia is driving companies to enhance customer loyalty in order to survive amid increasingly fierce competition. This study aims to analyze the influence of product quality and brand trust on customer loyalty toward Bioaqua facial moisturizers in Depok. This study employed a quantitative method, with data collected through a questionnaire distributed to a sample of 96 respondents selected using purposive sampling. The selection criteria included residing in Depok, being female, being at least 17 years old, and having purchased and used Bioaqua facial moisturizers at least twice. Data analysis was performed using IBM SPSS version 29 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results of the study indicate that, when considered individually, product quality does not have a significant effect on customer loyalty, whereas brand trust does have a significant effect on customer loyalty. When considered together, product quality and brand trust have a significant effect on customer loyalty, accounting for 68.1% of the variance. These findings suggest that brand trust is the more dominant factor in shaping customer loyalty among users of Bioaqua facial moisturizer in Depok.